2021
DOI: 10.1097/ee9.0000000000000156
|View full text |Cite
|
Sign up to set email alerts
|

The association between prenatal concentrations of polybrominated diphenyl ether and child cognitive and psychomotor function

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In the five other studies that studied association between prenatal maternal levels of PBDEs and attention or hyperactivity scores, null associations were reported (Adgent et al., 2014 ; Gascon et al., 2011 ; Julvez et al., 2021 ; Sagiv et al., 2015 ; Solazzo et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the five other studies that studied association between prenatal maternal levels of PBDEs and attention or hyperactivity scores, null associations were reported (Adgent et al., 2014 ; Gascon et al., 2011 ; Julvez et al., 2021 ; Sagiv et al., 2015 ; Solazzo et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve publications assessed inattention or hyperactivity subscales through a range of tools, including the CBCL, Conners DSM‐IV, CPT, BASC, SDQ and TEA‐Ch (Gascon et al., 2011 ; Kiciński et al., 2012 ; Eskenazi et al., 2013 ; Adgent et al., 2014 ; Chen, Yolton, et al., 2014 ; Gump et al., 2014 ; Cowell et al., 2015 ; Julvez et al., 2021 ; Ji et al., 2019 ; Sagiv et al., 2015 ; Solazzo et al., 2021 ; Vuong, Yolton, Xie, et al., 2017 ). Four of these studies observed statistically significant associations related to prenatal PBDE levels: the CHAMACOS cohort reported an association between Sum PBDEs and increased CBCL‐attention problems and DSM‐IV‐inattention problems at 5 and 7 years (Eskenazi et al., 2013 ); The HOME cohort reported an association between BDE‐47 and increased BASC‐hyperactivity problems (Chen, Yolton, et al., 2014 ); Ji et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acetaminophen-pathway interactions in association with neurodevelopment. References [ 61 , 62 , 63 , 64 ] are cited in the supplementary materials…”
mentioning
confidence: 99%